2018
DOI: 10.14238/pi58.6.2018.263-8
|View full text |Cite
|
Sign up to set email alerts
|

Depression in children with thalassemia major: prevalence and contributing factors

Abstract: Background Thalassemia major is a chronic disease requiring lifetime treatment. A recent study showed that 11-62% of thalassemia patients developed depression, which is associated with high morbidity and mortality. Understanding the extent of the problem related to depression and its contributing factors is important for early management. Objective To determine the prevalence and contributing factors for depression in children with thalassemia major. Methods This cross-sectional observational analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…Children with thalassemia faced stressful effects throughout their lives, including frequent blood sampling for laboratory tests, frequency of transfusions and frequent subcutaneous injections and oral therapy of iron chelator drugs, all of which mad patients vulnerable to psychiatric loads such as depression and anxiety (Pattanashetti et al 2017). Venty's study showed no correlation between the frequency of blood transfusions, pre-transfusion hemoglobin levels and depression (Venty et al 2018). However, it was different from other studies which showed a correlation between the frequency of blood transfusion and depression.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Children with thalassemia faced stressful effects throughout their lives, including frequent blood sampling for laboratory tests, frequency of transfusions and frequent subcutaneous injections and oral therapy of iron chelator drugs, all of which mad patients vulnerable to psychiatric loads such as depression and anxiety (Pattanashetti et al 2017). Venty's study showed no correlation between the frequency of blood transfusions, pre-transfusion hemoglobin levels and depression (Venty et al 2018). However, it was different from other studies which showed a correlation between the frequency of blood transfusion and depression.…”
Section: Resultsmentioning
confidence: 64%
“…Blood transfusion more often caused an increase in school absenteeism and affects patients interacting socially with their peers. Therefore, they felt isolated and vulnerable to depression (Venty et al 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted by (Venty et al, 2018), on 64 thalassemic children aged 7_18 years, there finding the mean Hb level was 7.18 [26] .…”
Section: Discussionmentioning
confidence: 90%
“…Usia remaja yang rentan perubahan emosional juga dapat menjadi faktor pendukung masalah emosional tersebut. 9,14 Masalah kedua yang paling banyak dialami oleh pasien adalah masalah conduct dengan proporsi 12%. Jumlah ini hampir sama dengan proporsi pada penelitian Behdani dkk 13 yang menunjukkan proporsi masalah conduct 11,9%.…”
Section: Pembahasanunclassified